Desvendando as orelhas-de-pau do Cerrado : um estudo taxonômico, ecológico e biotecnológico de fungos corticioides e poroides - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
In the class Agaricomycetes, Basidiomycota, there is a large group of lignicolous fungi traditionally known as aphyllophoroid. This group includes species of macrofungi, usually not- lamellate, where there are subgroups classified as poroids, corticioids, hydnoids, and stereoids, grouped from the morphology of the basidiomata and growth habits.Corticioid and poroid fungi are widely known for their efficiency in wood decomposition, nutrient cycling, and biotechnological applications. Despite being one of the most studied groups of fungi in the world, data on diversity and geographical occurrence patterns in Brazil are insufficient, especially in understudied areas, including the Cerrado. Thus, we aimed to increase the knowledge about diversity, phylogeny, geographic distribution, and ecological patterns of corticioid and poroid fungi from Cerrado through an extensive literature review, field expeditions, and exsiccate review. The literature review allowed us to identify the state of the art, the trends and gaps in knowledge, and the history of research on these fungi from the Cerrado, along with a list of species found in the biome so far. We found 387 records and 223 species, while 94 species are new additions to the checklists published in the last decade. Six of the listed species are endemic to Cerrado and 29, although they occur in other regions of the world, in Brazil there are only records in the biome. The low number of trained mycologists, lack of investment, deficient data from unexplored areas of the biome, and few long-term studies are obstacles to understanding the species richness of the biome and its biological, ecological, and evolutionary aspects. Thus, based on this problem, we focused our taxonomic studies on areas poorly studied in the Goiás state, where field expeditions in important conservation units of the biome were carried out, as well as the taxonomic revision of the fungarium of the State University of Goiás (HUEG-Fungi) which has one of the most important collections of Cerrado fungi. Between collections and revisions of the HUEG-Fungi collection, approximately 1000 specimens were analyzed. Of these, Furtadomyces sumptuosos is described as new to science, 20 as new occurrences from Cerrado, 20 from the Midwest region, and 24 from Goiás. A DNA database with about 100 samples of this material was also created. These new contributions increase the knowledge about these organisms in the country and the understanding of phylogenetic relationships of specific groups. Furthermore, the discovery of an unknown diversity may encourage new study approaches, such as biotechnology and ecology.
Unraveling the bracket fungi of the Cerrado : a taxonomic, ecological and biotechnological study of corticioid and poroid fungi
Keywords: Agaricomycetes; Basidiomycota; Filogenia; Fungos lignícolas; Macrofungos; Savana Brasileira; Taxonomia; Fungos; Agaricomycetes; Basidiomycota; Brazilian Savanna; Lignicolous fungi; Phylogeny; Macrofungi; Taxonomy; CIENCIAS BIOLOGICAS; BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::MICOLOGIA